2019
DOI: 10.1038/s41598-019-55663-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of melatonin and Bmal1 in the regulation of PI3K/AKT pathway components and cellular survival

Abstract: The circadian rhythm is driven by a master clock within the suprachiasmatic nucleus which regulates the rhythmic secretion of melatonin. Bmal1 coordinates the rhythmic expression of transcriptome and regulates biological activities, involved in cell metabolism and aging. However, the role of Bmal1 in cellular- survival, signaling, its interaction with intracellular proteins, and how melatonin regulates its expression is largely unclear. Here we observed that melatonin increases the expression of Bmal1 and both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 58 publications
1
61
0
Order By: Relevance
“…Melatonin actions were also reflected in the recovery of the phase relationship between Bmal1 and Per2 in rat adrenal cultures [57]. Recently, it was shown that melatonin controls the expression of Bmal1 through PI3K/AKT signaling [58]. Thus, our results point to the relevance of the potential modulatory effect of melatonin in the circadian clock of CP epithelial cells, which are known to express melatonin receptors (MT1 and MT2) [59] and to be involved in the chronobiotic action of melatonin [60].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin actions were also reflected in the recovery of the phase relationship between Bmal1 and Per2 in rat adrenal cultures [57]. Recently, it was shown that melatonin controls the expression of Bmal1 through PI3K/AKT signaling [58]. Thus, our results point to the relevance of the potential modulatory effect of melatonin in the circadian clock of CP epithelial cells, which are known to express melatonin receptors (MT1 and MT2) [59] and to be involved in the chronobiotic action of melatonin [60].…”
Section: Discussionmentioning
confidence: 99%
“…In this term, we have indicated that tolerance to ischemic injury changes according to the time of day in which the injury occurs and the underlying mechanism of this tolerance includes circadian clock genes, specifically Bmal1, which is also regulated by the phosphorylation of AKT signaling pathway [24]. Consistently, Bmal1 expression is enhanced following melatonin treatment following ischemic brain injury in mice and this increase is blocked when the survival kinase AKT inhibitors are present [26]. In addition to the transcriptional control of Bmal1 gene, melatonin may also regulate clock genes by stabilizing the protein through the inhibition of the ubiquitin-proteasome system [28].…”
Section: Justification Of Use Of Melatonin In Stroke Treatmentmentioning
confidence: 96%
“…Of these genes, the six core clock genes are known as Per1 and Per2, Cry1 and Cry2, Clock and Bmal1 [24,25]. We have reported that melatonin regulates Bmal1 expression under normal conditions in vitro after hypoxia and in vivo after ischemic stroke [26]. Interestingly, in parallel with the highest blood concentrations of melatonin, the ischemic stroke incidence is lowest at the midnight hours in human [27].…”
Section: Justification Of Use Of Melatonin In Stroke Treatmentmentioning
confidence: 99%
“…Previous studies observed that the Akt was significantly phosphorylated 2 h after melatonin treatment, and its phosphorylation lasted for up to 24 h. The expression of glial-cell-line-derived neurotrophic factor (GDNF) in the CA3 area was significantly increased after 6 h of melatonin treatment. After 24 h, the GDNF was mainly secreted by astrocytes [ 248 , 249 ].…”
Section: Translational Applications Of Melatonin Against Nddsmentioning
confidence: 99%